The Effect of Product, Price, Distribution, and Promotion on The Purchase Decision of Rice Seed Product in Jember - Hikmah, Nurul; Dewi, Liliana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The background of this research is the increase of return on sales of rice seeds product and the failure to achieve the sales target in 2021 which occurred at CV Bunga Tani Sejahtera, a producer of rice and corn seeds. Based on complaint data throughout 2021 indicate that there are problems with product, price, distribution and promotions, so evaluation and improvement are necessary. The purpose of this study was to determine the effect of product, price, distribution, and promotion on purchase decision of rice seed product in Jember. This study used 210 respondents that collected from four sub-districts in Jember, namely Balung, Gumukmas, Tanggul and Mayang. This research is quantitative research with multiple linear regression analysis method. The result showed that there is effect of product, price, and promotion on purchase decision of rice seed products in Jember. Meanwhile, distribution has no influence on purchase decision. Simultaneously, product, price, distribution, and promotion have an influence on the purchase decision of rice seed products in Jembe. The dominant influence on the purchase decision is product. The company is expected to improve product, evaluate price, and expand the promotion of rice seed products so the sales return can be reduced in the following years and market can develop.